SISTEM SILVIKULTUR TEBANG PILIH UNTUK MITIGASI PERUBAHAN IKLIM MELALUI KERANGKA REDD+ - Tigor Butarbutar (Jurnal Analisis Kebijakan Kehutanan, 2014)
Indonesia has committed for climate change mitigation especially in the forestry sector by REDD+ (Reducing Emissions from Deforestation and Degradation) scheme  and also through conservation, sustainable forest management and enhancement of carbon stocks. Silvicultural system is the process for planting, tending, cutting, changing a certain forest stand  for wood production another product .  The method in this study is a desk study/systematic review. The decline in the rate of forest degradation in REDD+ related to silvicultural practices such as harvesting techniques, tending of residues standing stock and replacement of wood stands or other forest products. Activities of carbon stock enhancement in REDD+ related to the silvicultural system such as enrichment planting and weed and pest eradication. While sustainable forest management activities in REDD+ was set up in Indonesia Selective Cutting and Planting (ISCP) system and its improvement. Reducing  emissions through decreasing or cambating forest degradation can be implemented sustainable forest management activities such as : 1) Carbon stock enhancement by implementing ISCP system consistently ; 2) Implementation of Reduced Impact Logging (RIL) ; 3) Maximizing enrichment planting by intensive silvicultur (SILIN); 4) Establisment of  conservation area in forest  concession; 5) Protection of forests; and 6) Restoration of logged-over  area ecosystem.